ANALISIS GAP KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN ANAK BERKEBUTUHAN KHUSUS PADA KLINIK PEDIATRIC AND NEURODEVELOPMENTAL THERAPY CENTER TOHUDAN COLOMADU - Wening Nalurita; Supawi Pawenang; Solichul Hadi Ahmad Bakri (JURNAL MANAJEMEN, 2019)
This study was conducted with the aim of (1) testing and analyzing the quality of services that include Tangible, Reliability, Responsiveness, Assurance and Empathy, both simultaneously and partially related to patient satisfaction Children with Special Needs at Tohudan Colomadu's Pediatric and Neurodevelopmental Therapy Center Clinic, (2) testing and analyzing the percentage of perceived service quality by patients with Special Needs at Tohudan Colomadu's Pediatric And Neurodevelopmental Therapy Center Clinic, and (3) testing and analyzing differences in the satisfaction level of perceived service quality with the expected service quality by patients of Children with Special Needs at Tohudan Colomadu's Pediatric And Neurodevelopmental Therapy Center Clinic. This research is a quantitative descriptive study, taking the population of patients who come and perform care in November 2018 - January 2019 with 1,800 patients with 100 patients as the samples. The method of data collection in this study uses a questionnaire as a tool to obtain data. The results showed that 1) Tangible, Reliability, Responsiveness, Assurance and Empathy, both simultaneously and partially related to patient satisfaction Children with Special Needs at Tohudan Colomadu's Pediatric and Neurodevelopmental Therapy Center Clinic, (2) percentage satisfaction level of perceived service quality by patients with Children with Special Needs at Tohudan Colomadu's Pediatric and Neurodevelopmental Therapy Center Clinic are more than 90%, and (3) there is no difference in satisfaction of service quality levels perceived service with the expected service quality by patients Children with Special Needs at Tohudan Colomadu's Pediatric And Neurodevelopmental Therapy Center Clinic.